Creativity Through Limited Resources: A Film Analysis of Simple Technology in Spare Parts (2015) - Tsamrotul Hidayah; M. Thoyibi (Ruang Kata, 2026)
The urgency of this research lies in the need for inclusive STEM education in under-resourced settings, demonstrating that low-cost technology can effectively foster innovation and active learning. The purpose of this study is to analyze the representation of the use of simple and low-cost technology in the context of education in the film Spare Parts (2015), as well as to examine how the characters in it demonstrate creativity, collaboration, and innovation in facing resource constraints, in order to identify educational values related to STEM empowerment conveyed through the film’s narrative. This research employs a qualitative descriptive method to analyze the representation of low-cost technology and STEM empowerment in the film Spare Parts (2015). The object of the study is the film directed by Sean McNamara, with scenes, dialogues, character actions, and visual elements as the primary data. Data collection was conducted through repeated film viewing, documentation of relevant scenes, and literature review of scholarly sources related to STEM education, educational technology, and film studies. Data analysis involved identifying, categorizing, and interpreting film elements based on the theoretical framework. To ensure data validity, theory triangulation was applied by integrating the Philosophy of Technology, STEM Empowerment Theory, and Sociocultural Learning Theory. This study concludes that Spare Parts (2015) portrays low-cost technology, creativity, and STEM learning as interconnected processes shaped by limited resources. The film shows that resource constraints can stimulate innovation through improvisation, trial and error, and collaborative problem-solving, where students transform simple materials into functional technology. By emphasizing student agency, mentorship, and teamwork, the film represents STEM empowerment as a holistic learning process that fosters confidence, creativity, and meaningful educational experiences in resource-limited contexts. The findings suggest that film-based narratives like Spare Parts can be used as pedagogical tools to inspire creativity, collaboration, and problem-solving while promoting affordable STEM learning approaches.